PENAMBAHAN TEPUNG UMBI DAHLIA, KEDELAI DAN BAWANG PUTIH SEBAGAI SUMBER PREBIOTIK UNTUK ENKAPSULASI PROBIOTIK [Addition of Flours from Dahlia Tuber, Soybean and Garlic as Prebiotic Sources for Probiotic Encapsulation] - . Ngatirah; Maria Ulfah (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2013)
ABSTRACT The research was conducted to study the effect of addition of flours made from dahlia tuber, soybean and garlic as the sources of natural prebiotic on the encapsulation of probiotic (Lactobacillus acidophilus Dad 13) with carragenan and chitosan. Carragenan and chitosan are potential encapsulating agents that can protect bacterial cells from unfavorable conditions. It is hypothesized that addition of natural prebiotics from dahlia tuber, soybean and garlic can stimulate the growth of probiotic (L. acidophilus Dad 13) in MRS broth medium. Parameters evaluated were size and weight of capsule, number of cells in the capsule, acid and bile salt resistance of the biocapsule produced from carragenan and chitosan added with flours of dahlia tuber, soybean and garlic as the sources of natural prebiotic. The randomized complete block design was used as the experimental design with two factors. The first factor was the encapsulating agents (A1 carragenan, A2 chitosan) and second factor was the sources of natural prebiotic (P1 dahlia tuber, P2 garlic, P3 soybean). The results showed that the type of encapsulating agent had an effect on weight, diameter and number of cells in the capsule but did not affect the acid and bile salt resistance. Addition of prebiotic flour to biocapsules had an effect on weight and diameter of capsules but no effect on acid and bile salt resistance and the number of cells. Addition of flour as prebiotic source from dahlia, garlic and soybean increased the cell number by 1 log cycle. Capsules made from chitosan with the addition of prebiotic source flour were lighter, had shorter diameter and lower cell reduction by acid (4.63-5.24 log cycle) than those made with carragenan (6.93-7.19 log cycle). Based on the acid resistance, the best biocapsules was made with chitosan and dahlia prebiotic flour. Keywords: carragenan, chitosan, Lactobacillus acidophilus Dad 13, natural prebiotic fluor, probiotic encapsulation